An Appraisal of Alvin Goldman’s Social Epistemology - Uzoigwe, Elias Ifeanyi E. (PREDESTINASI, 2020)
This work is aimed at giving an insight into the issues raised by Goldman in his argument that social epistemology is ‘real epistemology’. Goldman wants to convince the mainstream epistemologists and the philosophical world in general that social epistemology is real epistemology by distinguishing between three forms of social epistemology: revisionist, preservationist, and expansionist. These three forms of social epistemology construed and proposed by Goldman differ in how they relate to the basic assumptions of traditional/classical epistemology. While acknowledging the various authors for their divergent views and contributions to social epistemic discourse, this work holds that though Goldman, more than any other social epistemologist, raised a fresh perspective in social epistemology, yet, there is a missing link in his submission. Goldman’s preservationist social epistemology, which he argued is “real epistemology”, fails to give at least, a spotlight on what this work calls historical social epistemology. This does not in any way downplay Goldman’s giant stride in awakening epistemologists from their slumber which led some scholars to include issues like analytic social epistemology, diagnostic social epistemology, naturalistic social epistemology, and political social epistemology in the epistemic lexicon; and by so doing, expanding the frontiers of the epistemic domain of philosophical enterprise. It is the position of this research that Goldman’s social epistemology elicited a renewed interest in epistemologists and scholars alike in the social dimension of knowledge. This work employs historical, conceptual, contextual, and textual methods of analyses.